2006
DOI: 10.1364/ol.32.000184
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated Raman X waves in ultrashort optical pulse filamentation

Abstract: We demonstrate that ultrashort pulse filamentation in liquids with strong Raman gain leads to the spontaneous formation of nonlinear X waves at a Raman-shifted wavelength. We measured as much as 75% energy conversion efficiency into a Raman X wave in ethanol starting from 1 ps pulses due to the group velocity matching between the pump and Raman X pulses. Large Raman gain of a weak seed signal was observed in water, associated with a strong spatiotemporal transformation of the seed into an X wave.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 15 publications
2
28
0
Order By: Relevance
“…The Raman pulse, which is generated and slowed down by the SRS process, forms a slowlight spatial soliton. Note that the slow-light process presented here has to be distinguished from the mechanism of group-velocity locking for the stimulated Raman X waves generation in ultrashort optical pulse filamention though the observations seem to be similar to those reported here [27].…”
supporting
confidence: 81%
“…The Raman pulse, which is generated and slowed down by the SRS process, forms a slowlight spatial soliton. Note that the slow-light process presented here has to be distinguished from the mechanism of group-velocity locking for the stimulated Raman X waves generation in ultrashort optical pulse filamention though the observations seem to be similar to those reported here [27].…”
supporting
confidence: 81%
“…In spite of this, a conversion efficiency of 75% to the Raman wavelength was measured for a 5 cm long ethanol cell. By using a delayed seed at the Raman shifted wavelength, Faccio et al (2007) showed that the temporal overlap of the seed with one of the split pulses from the pump leads to the preferential excitation of a single set of X-tails of the Raman X pulse, i.e., a half Raman-X on the blue or on the red side of the Stokes wavelength. This suggests that the Raman X-wave, as for the pump, is formed by two half-X waves which are the red (or blue) legs of a blueshifted (or redshifted) X-wave with a frequency gap.…”
Section: Frequency Conversion To Raman-excited Modes By Filamentsmentioning
confidence: 99%
“…The so-called nonlinear X waves were observed in phasemismatched SHG processes [24,25] (recently also in a different regime in [26]), as well as investigated in Kerr media [27][28][29][30]. The nonlinear X waves are weakly localized nondiffracting and nondispersing wave packets characterized by a nonseparable spatiotemporal profile (propagation invariant solutions) [31,32], accessible in the normal group-velocity dispersion regime, the formation of which is triggered by conical emission [33].…”
Section: Introductionmentioning
confidence: 99%